Making Mesopotamia - Geography and Empire in a Romano-Iranian Borderland - Cameron, Hamish. (Impact of Empire, 2019)
In Making Mesopotamia: Geography and Empire in a Romano-Iranian Borderland , Hamish Cameron examines the representation of the Mesopotamian Borderland in the geographical writing of Strabo, Pliny the Elder, Claudius Ptolemy, the anonymous Expositio Totius Mundi, and Ammianus Marcellinus. This inter-imperial borderland between the Roman Empire and the Arsacid and Sasanid Empires provided fertile ground for Roman geographical writers to articulate their ideas about space, boundaries, and imperial power. By examining these geographical descriptions, Hamish Cameron shows how each author constructed an image of Mesopotamia in keeping with the goals and context of their own work, while collectively creating a vision of Mesopotamia as a borderland space of movement, inter-imperial tension, and global engagement.